2020
DOI: 10.1186/s12886-020-01747-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of total corneal astigmatism with a rotating Scheimpflug camera in keratoconus

Abstract: Background To analyze mean corneal powers and astigmatisms on anterior, posterior, and total cornea in patients with keratoconus as calculated according to various keratometric measurements using a Scheimpflug camera. Methods We examined the left eyes of 64 patients (41 males and 23 females; mean age 29.94 ± 6.63 years) with keratoconus. We measured simulated K (Sim-K), posterior K, true net power (TNP) and four types of total corneal refractive powers (TCRP). We then used the obtained values to analyze mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…TCRP can be measured over the apex (TCRP apex ) or the pupil (TCRP pupil ). Significantly higher mean K values have been found with TCRP apex measured at multiple optical zones [24]. Although this may be of limited relevance in patients with central cones, using TCRP pupil in peripheral cones would be less likely to overestimate corneal power, decreasing the likelihood of hyperopia postoperatively.…”
Section: Preoperative Considerationsmentioning
confidence: 87%
See 1 more Smart Citation
“…TCRP can be measured over the apex (TCRP apex ) or the pupil (TCRP pupil ). Significantly higher mean K values have been found with TCRP apex measured at multiple optical zones [24]. Although this may be of limited relevance in patients with central cones, using TCRP pupil in peripheral cones would be less likely to overestimate corneal power, decreasing the likelihood of hyperopia postoperatively.…”
Section: Preoperative Considerationsmentioning
confidence: 87%
“…Pentacam provides multiple measurements of corneal power, including simulated K (SimK), true net power (TNP), equivalent keratometry reading (EKR), and total corneal refractive power (TCRP). Studies comparing these parameters note that TCRP [5,23 ] and TNP [24] measure flatter values compared with SimK, whereas SimK values were significantly greater than EKR at increased corneal zone diameters [25].…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…Moreover, the group also found that the TCRP may be greater than or less than simK depending on the measurement area. 39 This highlights the need for further research to help inform clinician interpretation of various topography-derived data and ultimately help guide appropriate integration of this information into IOL power calculation.…”
Section: Estimation Of Corneal Powermentioning
confidence: 99%
“…Anterior segment optical coherence tomography (OCT) and Scheimpflug imaging are imaging modalities that can directly measure the anterior and posterior corneal surfaces and assess net corneal astigmatism. 8–12 OCT has several advantages over Scheimpflug imaging; modern OCT systems have higher axial resolution, scan at faster speeds, and can use custom topography software to reduce motion error. 11,13,14…”
mentioning
confidence: 99%
“…Anterior segment optical coherence tomography (OCT) and Scheimpflug imaging are imaging modalities that can directly measure the anterior and posterior corneal surfaces and assess net corneal astigmatism. [8][9][10][11][12] OCT has several advantages over Scheimpflug imaging; modern OCT systems have higher axial resolution, scan at faster speeds, and can use custom topography software to reduce motion error. 11,13,14 The goal of this study was to determine the accuracy and repeatability of net corneal astigmatism measured with a spectral-domain OCT system in keratoconic patients and compare them with a Scheimpflug imaging topographer using different analytic zone diameter (3 mm vs 4 mm) and map centration (corneal vertex vs pupil center).…”
mentioning
confidence: 99%